2020
DOI: 10.1007/s10928-020-09706-z
|View full text |Cite
|
Sign up to set email alerts
|

Integration of physiological changes during the postpartum period into a PBPK framework and prediction of amoxicillin disposition before and shortly after delivery

Abstract: The objective of this study was to develop a physiologically based pharmacokinetic (PBPK) model for amoxicillin for nonpregnant, pregnant and postpartum populations by compiling a database incorporating reported changes in the anatomy and physiology throughout the postpartum period. A systematic literature search was conducted to collect data on anatomical and physiological changes in postpartum women. Empirical functions were generated describing the observed changes providing the basis for a generic PBPK fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 117 publications
(109 reference statements)
1
31
0
Order By: Relevance
“…After delivery, many of the physiologic changes associated with pregnancy take weeks to months to revert to their prepregnancy baseline (17). Studies on antibiotic pharmacology have demonstrated marked alterations in drug pharmacokinetics (PK) between early (2-3 days post-delivery) and late (>4 months postdelivery) postpartum periods (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…After delivery, many of the physiologic changes associated with pregnancy take weeks to months to revert to their prepregnancy baseline (17). Studies on antibiotic pharmacology have demonstrated marked alterations in drug pharmacokinetics (PK) between early (2-3 days post-delivery) and late (>4 months postdelivery) postpartum periods (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies in pregnant populations often compare pregnant PK with the postpartum period, which may not be the equivalent of the nonpregnant state. Simulations of pregnancy/postpartum ratios improved when we developed postpartum populations based on recently published physiological data for the postpartum period (Dallmann, Himstedt et al., 2020) compared to simulations obtained from using a healthy, nonpregnant female population.…”
Section: Discussionmentioning
confidence: 99%
“…( Dallmann, Himstedt et al (2020). If postpartum data were not available for a specific parameter, it was assumed to be the same as the nonpregnant population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations